Safety and activity of ibrutinib in combination with nivolumab in patients with relapsed non-Hodgkin lymphoma or chronic lymphocytic leukaemia: a phase 1/2a study. Issue 2 (February 2019) - Younes, Anas; Brody, Joshua; Carpio, Cecilia; Lopez-Guillermo, Armando; Ben-Yehuda, Dina; Ferhanoglu, Burhan; Nagler, Arnon; Ozcan, Muhit; Avivi, Irit; Bosch, Francesc; Caballero Barrigón, Maria Dolores; Hellmann, Andrzej; et al.
Summary: Background: Preclinical studies have shown synergistic antitumour effects between ibrutinib and immune-checkpoint blockade. The aim of this study was to assess the safety and activity of ibrutinib in combination with nivolumab in patients with relapsed or refractory B-cell malignant diseases. Methods: We did a two-part, open-label, phase 1/2a study at 21 hospitals in Australia, Israel, Poland, Spain, Turkey, and the USA. The primary objective of part A (dose escalation) was to assess the safety of daily oral ibrutinib (420 mg or 560 mg) in combination with intravenous nivolumab (3 mg/kg every 2 weeks) to ascertain a recommended phase 2 dose in patients with relapsed or refractory high-risk chronic lymphocytic leukaemia or small lymphocytic lymphoma (del17p or del11q), follicular lymphoma, or diffuse large B-cell lymphoma. Dose optimisation was investigated using a modified toxicity probability interval design. The primary objective of the part B expansion phase was to establish the preliminary activity (the proportion of patients who achieved an overall response) of the combination of ibrutinib and nivolumab in four cohorts: relapsed or refractory high-risk chronic lymphocytic leukaemia or small lymphocytic lymphoma (del17p or del11q), follicular lymphoma, diffuse large B-cell lymphoma, and Richter's transformation. All participants who received at least one dose of treatment were included in the primary analysis and analyses were done by disease cohort. This trial is registered withClinicalTrials.gov, numberNCT02329847 . The trial is ongoing. Findings: Between March 12, 2015, and April 11, 2017, 144 patients were enrolled in the study. Three patients died before receiving study treatment; thus, 141 patients were included in the analysis, 14 in part A and 127 in part B. One dose-limiting toxicity (grade 3 hyperbilirubinaemia) was reported at the 420 mg dose in the diffuse large B-cell lymphoma cohort, which resolved after 5 days. The combination of ibrutinib and nivolumab led to overall responses in 22 (61%) of 36 patients with high-risk chronic lymphocytic leukaemia or small lymphocytic lymphoma, 13 (33%) of 40 patients with follicular lymphoma, 16 (36%) of 45 patients with diffuse large B-cell lymphoma, and 13 (65%) of 20 patients with Richter's transformation. The most common all-grade adverse events were diarrhoea (47 [33%] of 141 patients), neutropenia (44 [31%]), and fatigue (37 [26%]). 11 (8%) of 141 patients had adverse events leading to death; none were reported as drug-related. The most common grade 3–4 adverse events were neutropenia (40 [28%] of 141 patients) and anaemia (32 [23%]). The incidence of grade 3–4 neutropenia ranged from eight (18%) of 45 patients with diffuse large B-cell lymphoma to 19 (53%) of 36 patients with chronic lymphocytic leukaemia or small lymphocytic lymphoma; incidence of grade 3–4 anaemia ranged from five (13%) of 40 patients with follicular lymphoma to seven (35%) of 20 patients with Richter's transformation. The most common serious adverse events included anaemia (six [4%] of 141 patients) and pneumonia (five [4%]). The most common grade 3–4 immune-related adverse events were rash (11 [8%] of 141 patients) and increased alanine aminotransferase (three [2%]). Interpretation: The combination of ibrutinib and nivolumab had an acceptable safety profile and preliminary activity was similar to that reported with single-agent ibrutinib in chronic lymphocytic leukaemia or small lymphocytic lymphoma, follicular lymphoma, and diffuse large B-cell lymphoma. The clinical response in patients with Richter's transformation was promising and supports further clinical assessment. Funding: Janssen R&D.